1999
DOI: 10.1073/pnas.96.15.8669
|View full text |Cite
|
Sign up to set email alerts
|

Medin: An integral fragment of aortic smooth muscle cell-produced lactadherin forms the most common human amyloid

Abstract: Aortic medial amyloid is a form of localized amyloid that occurs in virtually all individuals older than 60 years. The importance and impact of the amyloid deposits are unknown. In this study we have purified a 5.5-kDa aortic medial amyloid component, by size-exclusion chromatography and RP-HPLC, from three individuals, and we have shown by amino acid sequence analysis that the amyloid is derived from an integral proteolytic fragment of lactadherin. Lactadherin is a 364-aa glycoprotein, previously known to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
161
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 40 publications
5
161
0
Order By: Relevance
“…A majority of the samples, including the control materials, contained amyloid in the extracellular matrix of the media. The deposits had the characteristics of medin-derived amyloid, 11,35 with small widely spread aggregates. Amyloid was often, but not always, observed as thin bands closely connected to the elastic laminae (Figure 1c and d).…”
Section: Histological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the samples, including the control materials, contained amyloid in the extracellular matrix of the media. The deposits had the characteristics of medin-derived amyloid, 11,35 with small widely spread aggregates. Amyloid was often, but not always, observed as thin bands closely connected to the elastic laminae (Figure 1c and d).…”
Section: Histological Findingsmentioning
confidence: 99%
“…9,10 The main amyloid fibril protein is medin (or AMed), which is a 50 amino-acid residue internal cleavage product of the precursor protein lactadherin. 11 Lactadherin is a 364 amino-acid residue protein found in many tissues [11][12][13][14] and has many proposed functions. 13,[15][16][17] To these functions we have added the ability of lactadherin to bind to elastin, and we have suggested that lactadherin acts as a linker between smooth muscle cells and elastin through its RGD-sequence at the N-terminal part and its medin part close to the C terminus.…”
mentioning
confidence: 99%
“…Nucleus formation requires a series of association steps of monomers, which are thermodynamically unfavorable, representing the rate-limiting step in amyloid fibril formation in vitro. Once the nucleus (n-mer) has been formed, further addition of monomers becomes thermodynamically favorable, resulting in rapid extension of amyloid fibrils in vitro.Many amyloidogenic proteins carry key regions that are specific to each amyloid protein (7,(27)(28)(29)(30). For an example, a 10-residue peptide of transthyretin can make fibrils that exhibit characteristics typical of the intact (127-amino acid residues) transthyretin (7).…”
mentioning
confidence: 99%
“…Many amyloidogenic proteins carry key regions that are specific to each amyloid protein (7,(27)(28)(29)(30). For an example, a 10-residue peptide of transthyretin can make fibrils that exhibit characteristics typical of the intact (127-amino acid residues) transthyretin (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation